eID and Self-Sovereign Identity Usage: An Overview - Daniela Pöhn (MDPI AG, 2021)
The COVID-19 pandemic helped countries to increase the use of their mobile eID solutions. These are based on traditional identity management systems, which suffer from weaknesses, such as the reliance on a central entity to provide the identity data and the lack of control of the user over her or his data. The introduction of self-sovereign identity (SSI) for e-government systems can strengthen the privacy of the citizens while enabling identification also for the weakest. To successfully initiate SSI, different factors have to be taken into account. In order to have a clear understanding of the challenges, but also lessons learned, we provide an overview of existing solutions and projects and conducted an analysis of their experiences. Based on a taxonomy, we identified strong points, as well as encountered challenges. The contribution of this paper is threefold: First, we enhanced existing taxonomies based on the literature for further evaluations. Second, we analyzed eID solutions for lessons learned. Third, we evaluated more recently started SSI projects in different states of their lifecycle. This led to a comprehensive discussion of the lessons learned and challenges to address, as well as further findings.